2016
DOI: 10.1007/s10661-016-5637-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and seasonal variations of 25 pharmaceutical residues in wastewater and drinking water treatment plants

Abstract: Thousands of tons of pharmaceuticals are introduced into the aqueous environment due to their incomplete elimination during treatment process in wastewater treatment plants (WWTPs) and water treatment plants (WTPs). The presence of pharmacologically active compounds in the environment is of a great interest because of their potential to cause negative effects. Furthermore, drugs can undergo different processes leading to the formation of new transformation products, which may be more toxic than the parent comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 44 publications
2
92
0
1
Order By: Relevance
“…In some locations, concentrations of the anti-inflammatory drug diclofenac have been reported to exceed predicted no-effect levels. 234,235 Concern is increasing that these compounds could damage freshwater and salt water marine species through a range of toxicological mechanisms, including endocrine disruption.…”
Section: Pesticidesmentioning
confidence: 99%
“…In some locations, concentrations of the anti-inflammatory drug diclofenac have been reported to exceed predicted no-effect levels. 234,235 Concern is increasing that these compounds could damage freshwater and salt water marine species through a range of toxicological mechanisms, including endocrine disruption.…”
Section: Pesticidesmentioning
confidence: 99%
“…While some parties believe that such concentrations are below toxic levels, many studies argue that the combined effects of pharmaceutical mixtures are unknown and must not be ignored. 2,3,[6][7][8] Numerous studies showed that the presence of pharmaceutical compounds in the environment has negative effects on both terrestrial and aquatic life. These effects include bacterial resistance to antibiotics, potential toxicity of chemical combinations, allergic complications, behavior and migratory patterns fertility in sh.…”
Section: Introductionmentioning
confidence: 99%
“…2,7,9 In addition, there is increasing concerns on the endocrine disruption caused by these pollutants. 2,6,8,10,11 That is the perturbation of endogenous hormone function by external chemicals, such as pharmaceuticals. Based on this, there is a need to seek new technologies to treat pharmaceutical compounds and personal care products in WWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the greatest concentration of the immunosuppressive agent, mycophenolic acid, in the River Vistula was found during spring whereas veterinary drugs from the group of benzimidazoles, designed to treat intestinal parasites, only occurred in river samples (River Gościnna in northern Poland) collected during autumn (Wagil et al 2015c). Considering that treated wastewater is a significant route through which APIs reach the environment, their concentrations in surface waters are likely to reflect the popularity and seasonal use of certain medications (Kot-Wasik et al 2016). This strongly advocates monitoring studies to be conducted continuously during the year rather than during a specific season.…”
Section: The State-of-art For Pharmaceutical Pollution Of Water Resoumentioning
confidence: 99%